State Financial Management Model - Susi ati; Umi Suswati Risnaeni; Indra Hidayatullah; Chumrotul Aini (Muhasabatuna : Jurnal Akuntansi Syariah, 2022)
Every government has a financial manager to ensure the implementation of development in his government. The president as the head of government holds the power to manage state finances which are delegated to the minister of finance and ministers or heads of institutions. The Minister of Finance holds the power to manage state finances as part of a government agency, the vital role of the Ministry of Finance is to manage state finances, assist state leaders in the field of finance and state assets based on Law no. 17 of 2003 concerning state finances and Law No. 1 of 2004 regarding the State Treasury and Law no. 15 of 2004 concerning Audit, Management and Financial Responsibility Country.